Antipsychotic Medications and Risk of Acute Coronary Syndrome in Schizophrenia: A Nested Case-Control Study - Liu, Hsing-Cheng; Yang, Shu-Yu; Liao, Ya-Tang; Chen, Chiao-Chicy; Kuo, Chian-Jue (PloS one, 2016)
This study assessed the risk of developing acute coronary syndrome requiring hospitalization in association with the use of certain antipsychotic medications in schizophrenia patients. A nationwide cohort of 31,177 inpatients with schizophrenia between the ages of 18 and 65 years whose records were enrolled in the National Health Insurance Research Database in Taiwan from 2000 to 2008 and were studied after encrypting the identifications. Cases (n = 147) were patients with subsequent acute coronary syndrome requiring hospitalization after their first psychiatric admission. Based on a nested case-control design, each case was matched with 20 controls for age, sex and the year of first psychiatric admission using risk-set sampling. The effects of antipsychotic agents on the development of acute coronary syndrome were assessed using multiple conditional logistic regression and sensitivity analyses to confirm any association. We found that current use of aripiprazole (adjusted risk ratio [RR] = 3.68, 95% CI: 1.27-10.64, p<0.05) and chlorpromazine (adjusted RR = 2.96, 95% CI: 1.40-6.24, p<0.001) were associated with a dose-dependent increase in the risk of developing acute coronary syndrome. Although haloperidol was associated with an increased risk (adjusted RR = 2.03, 95% CI: 1.20-3.44, p<0.01), there was no clear dose-dependent relationship. These three antipsychotic agents were also associated with an increased risk in the first 30 days of use, and the risk decreased as the duration of therapy increased. Sensitivity analyses using propensity score-adjusted modeling showed that the results were similar to those of multiple regression analysis. Patients with schizophrenia who received aripiprazole, chlorpromazine, or haloperidol could have a potentially elevated risk of developing acute coronary syndrome, particularly at the start of therapy.